نحو تعزيز تمويل المشروعات الصغيرة والمتوسطة من خلال التمويل الجماعي وإقراض النظير للنظير: Toward Enhanced SME’s Financing Through Crowdfunding and Peer- to- Peer Lending - صخري عبد الوهاب (Journal of North African Economies, 2025)
This Study aims to know the extent to which Crowdfunding and Peer-to-Peer Lending can bridge the financing gap of Small and Medium-Sized Enterprises, Especially in light of rejection of it by traditional lending and financing Agencies, In addition to what these new alternatives know of a qualitive leap at the international level, the descriptive and analytical methods was relied upon as required by the nature of the topic, the research paper concluded that crowdfunding is witnessing a high development in the largest Global Economies, Algeria also recorded its first steps of some digital Platforms, Moving to the leader role of peer-to-peer lending in order to support SME’s .